2012
DOI: 10.1016/j.jcrs.2012.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral uveitis after phakic intraocular lens implantation and management with adalimumab

Abstract: A 25-year-old woman with myopia who had an AC pIOL implantation in the left eye and posterior chamber pIOL implantation in the right eye developed bilateral granulomatous panuveitis 2 months after the second surgery. Physical examination showed bilateral Koeppe and Busacca nodules. Fluorescein angiography showed diffuse vascular and retinal pigment epithelial leakage in both eyes. With assessment of sympathetic ophthalmia, treatment with a high-dose systemic steroid was started. Oral cyclosporine and azathiopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 6 publications
0
15
0
1
Order By: Relevance
“… 19 However, the number of SO patients is limited; thus, such encounters are limited to case reports. 15 , 16 , 19 Despite the limited availability of approved non-steroidal immunosuppressive therapy for non-infectious uveitis in Japan, these two detailed cases show the successful treatment of SO with adalimumab. These two cases also reveal the importance of the early initiation of adalimumab in glaucoma or diabetic patients, in order to avoid the side effects of corticosteroid treatment.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“… 19 However, the number of SO patients is limited; thus, such encounters are limited to case reports. 15 , 16 , 19 Despite the limited availability of approved non-steroidal immunosuppressive therapy for non-infectious uveitis in Japan, these two detailed cases show the successful treatment of SO with adalimumab. These two cases also reveal the importance of the early initiation of adalimumab in glaucoma or diabetic patients, in order to avoid the side effects of corticosteroid treatment.…”
Section: Discussionmentioning
confidence: 87%
“… 14 Soheilian et al first reported on the effectiveness of adalimumab for a patient with refractory SO after phakic intraocular lens implantation. 15 Kase et al described the use of adalimumab therapy for refractory paediatric SO after trauma. 16 These cases show the successful use of adalimumab therapy for SO patients with a history of glaucoma filtration surgery.…”
Section: Discussionmentioning
confidence: 99%
“…So konnte bei einem 7-jährigen Kind mit therapierefraktärer SO Infliximab erfolgreich eingesetzt werden [37]. Ebenfalls zeigte Adalimumab bei SO nach Trauma im Kindesalter ein gutes Ergebnis [38]. Weitere Kasuistiken zu Anti-TNF-α-Therapie und SO liegen u. a. von Payal u.…”
Section: Bildgebende Verfahrenunclassified
“…4 Another case of an adult with SO refractory to multiple immunosuppressants achieved inflammation resolution with addition of adalimumab, a recombinant human monoclonal anti-TNF-α antibody dosed subcutaneously. 5 In a series of 131 patients with refractory uveitis, addition of adalimumab reduced immunosuppressive load by 50% in 85% of patients. 6 …”
Section: Commentmentioning
confidence: 99%